THE INVESTIGATION DIFFICULTY LEVEL OF PERCEPTION INTO BAROQUE PERIOD FOR PIANO REPERTOIRE OF STUDENTS PİANO EDUCATION - İzzet YÜCETOKER (Fırat University, 2019)
The aim of this study is to examine the music education department at the faculty of education students studying piano at the difficulty level of perception of auxiliary instruments for baroque works sung by several variables. The universe of this research using quantitative methods made 2014 - 2015 academic year studying in Nigde and Necmettin Erbakan University studying in the faculty of education music education department connected to form 281 students. Research data, Yucetoker and Senturk (2014) "developed by Perception Scale for the Level of difficulty Baroque Piano Works" and collected. The analysis of the survey data as well as descriptive statistics for each variable t test, one way ANOVA and Tukey significance test is used SPSS 16.0 software package for the analysis of these data is used. The piano students baroque works according to the findings of the survey technique and musicality that have difficulties due to the overall structure and grade levels increases appeared to be increased in the correct proportion of these challenges. Besides, according to the students who like to sing the baroque works like a significant difference was found between the students. These results challenge several recommendations for changing the perception of the baroque works of students has been developed in the light.